2019
DOI: 10.2528/pierm19051802
|View full text |Cite
|
Sign up to set email alerts
|

A Small Cost-Effective Super Ultra-Wideband Microstrip Antenna With Variable Band-Notch Filtering and Improved Radiation Pattern With 5g/Iot Applications

Abstract: In this work, a new design of small microstrip antenna with variable band-notched filtering characteristic for super ultra-wideband (UWB) applications including 5G/IoT networks is presented. In the proposed structure by creating steps with optimized appropriate sizes and angles in the lower edges of the quasi-square patch antenna and by a new technique of modifying the ground plane, more efficient radiation patterns and characteristic impedance are achieved. Moreover, the omnidirectional low cross-polarized H-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…From [6] and [8], it can be stated that though the bandwidth and BDR ratio of the referred antennas are greater than the designed antenna, the gain and bandwidth are less in the published work than the proposed SWB antenna that covers a larger band of frequency than the published work. However, from [9,10,13,14,16,17,25,27,28], it has been observed that the proposed SWB antenna has a wide frequency range, enhanced bandwidth, high peak gain, and high BDR ratio though the antenna is smaller in size than the referred SWB antenna. The superior performance of the proposed SWB antenna in terms of size, bandwidth, and gain makes the proposed antenna most suitable for various microwave applications.…”
Section: Design and Analysis Of Fractal Swb Antennamentioning
confidence: 99%
See 1 more Smart Citation
“…From [6] and [8], it can be stated that though the bandwidth and BDR ratio of the referred antennas are greater than the designed antenna, the gain and bandwidth are less in the published work than the proposed SWB antenna that covers a larger band of frequency than the published work. However, from [9,10,13,14,16,17,25,27,28], it has been observed that the proposed SWB antenna has a wide frequency range, enhanced bandwidth, high peak gain, and high BDR ratio though the antenna is smaller in size than the referred SWB antenna. The superior performance of the proposed SWB antenna in terms of size, bandwidth, and gain makes the proposed antenna most suitable for various microwave applications.…”
Section: Design and Analysis Of Fractal Swb Antennamentioning
confidence: 99%
“…[12] proposes a skull shaped structure with a slotted rectangular partial ground plane design with a fractional bandwidth of 160.66% ranging from 3 GHz to 27.5 GHz and a peak gain of 6.3 dBi. In [13], a quasi-square with proper sizes and angles on the lower edges of the patch and ground plane with two circular slots is presented, which is a characteristic for SWB applications. The bandwidth is obtained from 3 GHz to 50 GHz with a variable gain of 1 to 9.47 dBi.…”
Section: Introductionmentioning
confidence: 99%
“…For reaching the hundreds of Exabyte, next mobile generations and new cellular communication systems will meet such requirements. Using new spectrum beyond sub-6 GHz frequencies could be one way to address this rising demand and satisfy the needs of greater than 10 Gbps peak and edge speeds of approaching 100 Mbps for extreme mobile broadband (eMBB) applications [1][2][3][4][5]. Furthermore, for optimal performance, wireless sensor networks such as ZigBee, LDWA, LoRa, WWAN, and mobile radio networks such as 2G, 3G, 4G, and soon 5G/6G (5th/6th Generation) require online data processing, artificial intelligence (AI), and machine learning (ML), and all of them need super ultra-wideband communication instruments and systems.…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet this increased capacity requirement to assist 5G extreme mobile broadband wireless application that require peak speeds of 10 Gbps and higher as well as edge speeds greater than 100 Mbps. With the availability of vast bandwidth at mmWave frequency the fifth generation EMBB standards can met by employing a straightforward signal interface as well as high-dimension phased arrays [2]. Because of the light weight, cost efficient, ease of manufacture and other characteristics, microstrip patch antennas are an excellent candidate for use in ultra-wideband wireless applications [3].…”
Section: Introductionmentioning
confidence: 99%